Performance Management Success A Best Practices and Implementation Guide for Leaders and Managers of All Organizations - Barth, Anthony L. (Management for Professionals,, 2018)
This book provides managers, leaders and practitioners with a dynamic framework that links several variables associated with performance management which can be applied across organizations and industries worldwide. Based on empirical evidence and experiences, this book provides a critical understanding of the interrelationship of organizational culture with performance management process (PMP) planning and implementation. The elements of the framework are approached from a macro-level-view and are balanced with conciseness and realism based on applied success studies, making this book a valuable educational, training and development resource tool for leaders and managers at all levels. The topic of performance in organizations is like the weather-everyone likes to talk about it, but few understand what is truly happening-or understand why? Individuals and organizations are no different when it comes to performance, regardless of performance level of focus: individual, team, unit, or organization-wide. Teams and organizations often miss opportunities to not only improve performance, but also leverage and sustain high performance. Organizational performance, organizational culture and organizational success are interrelated and should reinforce one another. This can be achieved through an effective performance management process (PMP) that lives, functions and thrives at multiple levels within institutions. This book will help organizations and institutions achieve performance management success by identifying comment elements, along with some patterned variation, that are applicable to a successful PMP. Featuring hands-on resource reference tools for immediate use and application, this book is useful for leaders, managers, scholars, students and policy makers in management, leadership, and organizational culture.